2009
DOI: 10.3346/jkms.2009.24.6.1004
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cytotoxic T Lymphocyte Antigen-4 Gene Polymorphisms and HLA Class II Alleles with the Development of Type 1 Diabetes in Korean Children and Adolescents

Abstract: We studied the association of cytotoxic T lymphocyte antigen-4 gene (CTLA4) polymorphisms with the development of type 1 diabetes (T1D) in Korean children and adolescents. A total of 176 Korean subjects (92 females and 84 males) with childhood-onset T1D were studied. The A/G polymorphism at position 49 in CTLA4 exon 1 and the C/T polymorphism at position -318 in the CTLA4 promoter were analyzed by PCR-RFLP methods. The genotype and allele frequencies of the CTLA4 polymorphisms in the T1D patients were not diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Baniasadi et al showed that the Ϫ318T allele conferred T1D susceptibility on north Indians (6), while Balic et al reported that the Ϫ318C/T variant did not influence the overall risk of T1D in Caucasians (5). In this study, we found no significant association of CTLA-4 Ϫ318C/T polymorphism with T1D in Tunisian patients, in agreement with published reports on populations with diverse ethnic backgrounds (5,6,8,19). Furthermore, a recent meta-analysis of 5,637 T1D patients and 6,759 controls demonstrated no association of the Ϫ318 variant with T1D (OR ϭ 0.92; 95% CI ϭ 0.45 to 1.89) after several confounders were controlled for (20).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Baniasadi et al showed that the Ϫ318T allele conferred T1D susceptibility on north Indians (6), while Balic et al reported that the Ϫ318C/T variant did not influence the overall risk of T1D in Caucasians (5). In this study, we found no significant association of CTLA-4 Ϫ318C/T polymorphism with T1D in Tunisian patients, in agreement with published reports on populations with diverse ethnic backgrounds (5,6,8,19). Furthermore, a recent meta-analysis of 5,637 T1D patients and 6,759 controls demonstrated no association of the Ϫ318 variant with T1D (OR ϭ 0.92; 95% CI ϭ 0.45 to 1.89) after several confounders were controlled for (20).…”
Section: Discussionsupporting
confidence: 82%
“…The genetic associations between the CTLA-4 polymorphic variants Ϫ318C/T, ϩ49A/G, and CT60A/G were previously investigated in different ethnic groups, but with inconsistent findings (6,17,19,30,35). CTLA-4 is now among the five replicated and established non-HLA loci, together with INS, PTPN22, IL2RA, and IFIH1 (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 43 published studies between CTLA-4 and T1D were identified according to our inclusion criteria, involving 8021 cases and 9570 controls (Nistico et al, 1996;Donner et al, 1997;Van der Auwera et al, 1997;Krokowski et al, 1998;Djilali-Saiah et al, 1998;Awata et al, 1998;Yanagawa et al, 1999;Hayashi et al, 1999;Abe et al, 1999;Takara et al, 2000;Lee et al, 2000;Ihara et al, 2001;Kamoun et al, 2001;Osei-Hyiaman et al, 2001;McCormack et al, 2001;Kikuoka et al, 2001;Cosentino et al, 2002;Fajardy et al, 2002;Cinek et al, 2002;Ma et al, 2002;Klitz et al, 2002;Wood et al, 2002;Ongagna et al, 2002;Mochizuki et al, 2003;Bouqbis et al, 2003;Zalloua et al, 2004;Haller et al, 2004;Ide et al, 2004;Ahmedov et al, 2006;Baniasadi et al, 2006;Ikegami et al, 2006;Saleh et al, 2008;Douroudis et al, 2009;Balic et al, 2009;Jung et al, 2009;Korolija et al, 2009;Ferreira et al, 2009;Benmansour el al., 2010;Ei Wafai et al, 2011;Philip and Isabel, 2011;…”
Section: Identification Of Eligible Studiesmentioning
confidence: 99%